The Role of Profitability, ESG Disclosure and Financing Decisions on Firm Value with Dividend Policy as a Mediating Variable (E-Jurnal Akuntansi, 2026)
In the Indonesian property and real estate sector, firm value fluctuated due to economic pressures, highlighting the need to understand the factors affecting it as an indicator of corporate performance and future prospects. This study aims to analyze the effect of profitability, ESG disclosure, and financing decisions on firm value with dividend policy as a mediating variable in property and real estate companies listed on the Indonesia Stock Exchange during the 2020-2024. The sample consists of 12 companies with 60 observations. Data were analyzed using panel data regression and the Sobel test. The results indicate that profitability and financing decisions have a positive effect on firm value, while ESG disclosure and dividend policy have no effect. Regarding dividend policy, profitability has a positive effect, whereas ESG disclosure and financing decisions have no effect. Dividend policy does not mediate variable relationships. Thus, firm value is determined by financial performance.
Keywords: Profitability; ESG Disclosure; Financing Decisions; Dividend Policy; Firm Value